RC Beams strengthened with HPFRCC: Experimental and numerical results - Daugevičius, Mykolas; Valivonis, Juozas; Skuturna, Tomas; Popov, Vladimir (Journal of Civil Engineering and Management, 2016)
The study analyses the behaviour of reinforced concrete beams strengthened with high-performance fibre-reinforced cementitious composite (HPFRCC). Six beams were divided into two equal groups and strengthened. In total, nine beams were tested, including three control beams that were not strengthened. Control beams were over-reinforced. The beams of the first group were strengthened in the compressed part while those of the second group were strengthened in the compressed and tensioned parts of the section. The experimental results of all tested beams were compared with numerical results. The positive and negative effects of strengthening the resistance and serviceability of the beams were experimentally determined. The obtained results showed that the load-carrying capacity of all strengthened beams increased and their deflections decreased; however, crack width in the beams of the second group increased while that of the beams of the first group decreased. The width of cracks increased because the number of cracks decreased. The findings of this study show a comparison of strains, deflections, cracking and load-carrying capacity and indicate that strengthening changed the failure of the beams.